Effectiveness of Team Quiz Method in Improving The Tajweed Learning and Student Activity at SDLB Putramanunggal Gombong - Budiono, Budiono (Universitas Sebelas Maret, 2019)
This study aims to determine the effectiveness of team quiz method to improve the tajweed learning and student activity on students with visual impairments in grade 4 at SDLB Putra Manunggal Gombong, Kebumen. This research is a classroom action research with 6 students as the research subjects. This study consisted of 2 cycles that each cycle has 2 times of meetings. The utilized instruments were test sheet, interview sheet, and observation sheet. Triangulation techniques was used to validate the data. The results showed that: 1) the team quiz method was effective in improving the tajweed learning and student activity that achieved a good category; 2) the tajweed learning was increased an average value in the first cycle by number 57,5 with 58,33% learning completeness whereas in the second cycle was 75 with 91,66% learning completeness; 3) the student activity was increased with an average score in the first cycle was 27 and in the second cycle was 35.